2022
DOI: 10.1186/s13570-022-00250-8
|View full text |Cite
|
Sign up to set email alerts
|

Can formalisation of pastoral land tenure overcome its paradoxes? Reflections from East Africa

Abstract: Legal frameworks for communal land rights in Ethiopia, Kenya, and Tanzania are now gaining momentum. Questions can be raised as to whether, how, and to what extent these frameworks take into account the disadvantages of formalising tenure and the complexities of pastoral resources. In this paper, we consider the impact of these challenges on the formalisation of communal ownership, beginning with an overview of how commons theory has influenced land governance policies and how it is applied to pastoral systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Importantly, people in local communities in these rangelands have knowledge that could benefit our understanding of local conditions, as well as strategies to adapt to changes in biodiversity and climate (IPBES et al 2019 ). Wilder rangelands specifically recognise that solutions to global challenges should be supported by, and ideally co-created with, the communities living in the rangelands, by recognising that ecosystems reflect many ecological processes, including those of indigenous peoples (Ogar et al 2020 ), for the restoration of degraded landscapes (Reyes-García et al 2019 ). The wilder rangelands concept incorporates traditional or indigenous knowledge systems that have evolved through livelihoods dependent on these ecosystems.…”
Section: Implementation Of Wilder Rangelandsmentioning
confidence: 99%
“…Importantly, people in local communities in these rangelands have knowledge that could benefit our understanding of local conditions, as well as strategies to adapt to changes in biodiversity and climate (IPBES et al 2019 ). Wilder rangelands specifically recognise that solutions to global challenges should be supported by, and ideally co-created with, the communities living in the rangelands, by recognising that ecosystems reflect many ecological processes, including those of indigenous peoples (Ogar et al 2020 ), for the restoration of degraded landscapes (Reyes-García et al 2019 ). The wilder rangelands concept incorporates traditional or indigenous knowledge systems that have evolved through livelihoods dependent on these ecosystems.…”
Section: Implementation Of Wilder Rangelandsmentioning
confidence: 99%
“…Investments in pastoral areas have included mining, alternative energy, conservation, irrigated farming, tourism, and more. Policies governing such investments have often been lacking, resulting in land, water, and green grabs in pastoral areas, and growing grievances among pastoral populations, along with disputes over land (Lind et al, 2020a;Nori, 2022d;Robinson and Flintan, 2022). Aid policies increasingly focus on humanitarian assistance, often resulting in a dependency on aid flows in some pastoral regions where drought strikes frequently, despite the rhetoric around resilience building, livelihood security, and social protection ; see also Chapters 6 and 7).…”
Section: Pastoral Policies: a Regional Overviewmentioning
confidence: 99%
“…In the same way, Behnke (1994) presented the importance of pastoral customary rules as robust and resilient and their techniques of land management are not as dysfunctional as it was once widely assumed. A recent review by Robinson and Flintan (2022) also indicated that state land policies in Ethiopia, Kenya, and Tanzania are not well matched with the socioecological basis of some of the rangeland situations.…”
Section: Understanding Pastoralism In Tropical Africamentioning
confidence: 99%